The HOOP study: robust evidence for perineal care? - McCandlish, R; Renfrew, M; Kettle, C; Garcia, J; Elbourne, D; Bowler, U (Mark Allen Healthcare, 2003)
Effective contemporary midwifery practice often combines the use of high level analytical skills with appropriate and unbiased communication of evidence to support women's decisions and choices. Although the results of sufficiently large randomized controlled trials provide the most robust evidence about comparative effectiveness of alternatives forms of care, all evidence should be subject to rigorous quality review, irrespective of its origins. This article demonstrates how criticisms that the conclusions of the HOOP trial were flawed and cannot be used to inform midwifery care for individual women, are wrong. In fact, HOOP provides clear and enduring evidence for women and midwives about important health outcomes and should be used to underpin discussion and practice of routine perineal care.